2010
DOI: 10.1098/rsbl.2010.0173
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size dimorphism is the most consistent explanation for the body size spectrum of Confuciusornis sanctus

Abstract: Evolutionary developmental biology Invited replySexual size dimorphism is the most consistent explanation for the body size spectrum of Confuciusornis sanctusRecently, we suggested that the size spectrum of Confuciusornis sanctus is best explained by sexual size dimorphism (SSD) and is compatible with a bird-like life history (Peters & Peters 2009). We find the criticism of Chiappe et al. (2010) interesting, but irrelevant to our main argument.Let us follow this argument from the beginning. Chiappe et al. (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…, 2008, 2010). Earlier workers have suggested that the skeletal proportions and the presence of tail feathers in this highly abundant Chinese bird are consistent with sexual size dimorphism within the known specimen sample (Peters & Peters, 2009, 2010).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…, 2008, 2010). Earlier workers have suggested that the skeletal proportions and the presence of tail feathers in this highly abundant Chinese bird are consistent with sexual size dimorphism within the known specimen sample (Peters & Peters, 2009, 2010).…”
Section: Resultsmentioning
confidence: 59%
“…, 1995; Chiappe et al. , 1999, 2008, 2009; Peters & Peters, 2009, 2010). One biomechanical analysis of the strength of their narrow primary feather rachises (Nudds & Dyke, 2010) and recent anatomical studies indicating restricted upstroke capabilities (Senter, 2006; Zhou & Zhang, 2007) suggest that Confuciusornis was not capable of vigorous flapping flight.…”
Section: Discussionmentioning
confidence: 98%
“…Interpretations of the similar feathers present in confuciusornithiforms have instead been dominated by suggestions that they were used for sexual display—their variable presence in the known specimens suggestive of sexual dimorphism [39,51,60,61]. However, recent morphometric studies have not been able to support or reject this hypothesis [45,51] and the function of these feathers remains controversial [62]. The variation in length and morphology observed among the tail feathers of enantiornithines may suggest they are also related to display, species recognition [63], or other forms of visual communication [64].…”
Section: Resultsmentioning
confidence: 99%
“…lifestyle specific and seasonal fluctuations 1 2 ) to overlay the intrinsic mosaic evolution of avian 9 and mammalian 29 brain development. As an extension, dimorphic segregation might also be discernible amongst the restored brains of fossil avians, and could be used to discriminate disputed sexual morphs accepting the constraints of adequate diagenetic retro-deformation and sample size 30 31 32 33 . More importantly, exact quantitative measure of different brain regions, especially the proportional enlargement of the forebrain, which has been qualitatively contested as an indicator of enhanced somatosensory integration and the capacity for flight 19 20 , requires further investigation.…”
Section: Resultsmentioning
confidence: 99%